Concerted Ring Opening and Cycloaddition of Chiral Epoxy Enolsilanes with Dienes1. Issue 25 (7th May 2015) - Krenske, Elizabeth H.; Lam, Sarah; Ng, Jerome P. L.; Lo, Brian; Lam, Sze Kui; Chiu, Pauline; Houk, Kendall N.
Abstract Silyl‐triflate‐catalyzed (4+3) cycloadditions of epoxy enolsilanes with dienes provide a mild and chemoselective synthetic route to seven‐membered carbocycles. Epoxy enolsilanes containing a terminal enolsilane and a single stereocenter undergo cycloaddition with almost complete conservation of enantiomeric purity, a finding that argues against the involvement of oxyallyl cation intermediates which have been previously proposed for these types of reactions. Reported are theoretical and experimental investigations of the cycloaddition mechanism. The major enantiomers of the cycloadducts are derived from SN2‐like reactions of the silylated epoxide with the diene, in which stereospecific ring opening and formation of the two new CC bonds occur in a single step. Calculations predict, and experiments confirm, that the observed small losses of enantiomeric purity are traced to a triflate‐mediated double SN2 cycloaddition pathway.